ANALISIS KEPUTUSAN INVESTASI PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Mia Debbiyanti Yunita; Yuniningsih yuniningsih (Fakultas Ekonomi dan Bisnis, Universitas Papua., 2020)
Investment activity in the capital market is one of the activities of allocating funds in the form of long-term assets in the hope of obtaining future profits. This research aims to determine the effect of liquidity, profitability, dividend policy, leverage on investment decisions and growth opportunity as variables moderation. The population used in this study is manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2014-2018 period of 150 companies. Samples were taken by purposive sampling method as many as 43 manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2014-2018 period. The type of data used is secondary data obtained from company financial statements. Data analysis method used is classical assumption test, multiple linier regression analysis, t test, f test, and test coefficient of determination. The result show that liquidity, profitability, dividend policy have no effect on the investment decisions. While the leverage have a negative significant effect on the investment decisions. And growth opportunity can not moderate the effect of leverage on the investment decisions. investment decisions of manufacturing companies on the Indonesia Stock Exchange must be able to allocate their funds appropriately to various assets in order to generate profits in the future so that they can be used to fund investment.